A Novel Subchannel and Power Allocation in IEEE 802.16 OFDMA Systems. Issue 2 (3rd March 2016) - Mostafavi, Mohammad; Niya, Javad Musevi
ABSTRACT: Lots of burst mapping algorithms have been proposed to optimize the two dimensional frame utilization in IEEE 802.16 OFDMA systems. However, almost all of the proposed algorithms only consider the frame usage optimization and do not consider the users' channel conditions. Some of the other researches have been focused on the power control and frequency allocation in the OFDMA-based systems. This paper aims to develop a novel resource allocation approach in IEEE 802.16 OFDMA systems with consideration of the two dimensional frame and the users' channel conditions. In order to further reduce the complexity of resource allocation, a new adaptive step size is proposed to speed up the convergence of the iterative optimal Lagrange multiplier computation. The expression for this step size is mathematically derived. The frequency and power allocation have been conducted in the subchannel and user level. The simulation results show that the throughput in terms of maximum sum rate (MSR) has been improved compared to static power control (the same power allocation to subchannels). Increasing the number of users increases the MSR improvement. This is due to the fact that the user diversity increases.